How to Enhance Islamic Education Learning Outcomes through an Integrated Literacy Approach in Madrasah? A Case Study - Anwariyah, Lulu'; Fanani, Ahmad Azis; Hidayah, Fathi; Baharun, Hasan (Jurnal Keislaman, 2024)
This research analyses how to improve learning outcomes through an integrated literacy approach in madrasah. This research uses a qualitative case study approach. The research subjects consisted of the principal, deputy head of student affairs, deputy head of curriculum, head of the library, teachers, and students. Data collection techniques use interview observation and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. The results showed that the experimental group experienced a significant increase in learning outcomes compared to the control group. An integrated literacy approach has proven effective in increasing students' understanding of subject matter, critical thinking skills, and interest in reading. This approach also helps students link knowledge from various scientific disciplines to make learning more meaningful and contextual. This research suggests that madrasah consider implementing integrated literacy as a learning strategy to improve the quality of education and student learning outcomes.